(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article argues that astrakhan skins drying process, skin surface shrinkage and energy consumption reduction can be achieved by accelerating the drying process and increasing the evaporation surface, its achieving theory, moisture evaporating amount, the analytical relationship characterizing moisture evaporation from the astrakhan skin surface, the moisture amount passing through and evaporating on the drying skin layer surface (epidermis, dermis, subcutaneous cell), and to accelerate the astrakhan skins drying, it has been proved expedient to ensure that moisture evaporation from the astrakhan skin surface is twofold